Scrub typhus in pregnancy: Maternal and fetal outcomes. (December 2016) - Rajan, Sudha J; Sathyendra, Sowmya; Mathuram, Alice J
Scrub typhus is an important unrecognized cause for undifferentiated acute febrile illness in India associated with poor fetal outcomes. Maternal and fetal outcomes among pregnant patients with scrub typhus presenting to a tertiary care university teaching hospital from January 2010 to July 2012 were studied. Scrub typhus was diagnosed by clinical criteria along with scrub ELISA positivity or an eschar. In total, 33 of 738 patients (4.5%) who were diagnosed with scrub typhus were pregnant; 57.6% were in the third trimester, 27.3% in the second, and only 15.2% in the first trimester; 69.7% required admission to intensive care. Mortality was low (3%, n  = 1) compared to 12.2% mortality reported previously. All patients were treated with Azithromycin. Poor fetal outcome was observed in 51.5% of these pregnancies with fetal loss occurring in 42.4% and preterm childbirth in 9.1%. Scrub typhus complicating pregnancy is associated with a poor fetal outcome despite treatment with Azithromycin. A majority require intensive care treatment for survival.